Co-creating a regional sustainability hub: conversational AI, community engagement, and local data for computing in place - Pittman, Daniel, author; Williams, Alyssa, author; Haring, Kerstin, author; Salo, Jessica, author; Newman, Gregory, author; Kennedy, Alexis, author; Newman, Sarah, author; Kalevela, Sylvester, author; ACM, publisher (Colorado State University. Libraries, 2025)
The Sustainability Hub is a community-driven digital infrastructure project that connects policymakers, researchers, and community members across Colorado through a shared platform for sustainability and well-being data. Grounded in a place-based computing approach, the Hub integrates conversational AI, open-source tools, and community asset mapping to support regional decision-making and resilience. This paper presents early-stage development and future directions. We introduce Bili, a natural language assistant that lowers technical barriers to data access and BiliCore, a framework for evaluating large language models in sustainability contexts. Another key component is the implementation of survey-informed Communities of Interest to support collaboration and engagement. We describe our co-design methodology, beta testing strategy, and participatory outreach efforts, offering a real-world case of computing in place that bridges technical innovation with social infrastructure.
Keywords: sustainability; computing in place; community engagement; participatory design; conversational AI; large language models; retrieval-augmented generation; human-computer interaction; natural language processing; geographic information systems